Implementation of decoy state protocol - Ali, Sellami; Saharudin, Shuhairi; Wahiddin, Mohamed Ridza (EuroJournals Publishing, Inc., 2009)
We report the experimental demonstration of decoy state QKD using commercial QKD system based on a standard bi-directional 'Plug & Play' set-up. By making simple modifications to a commercial quantum key distribution system, decoy state QKD allows us to achieve much better performance than QKD system without decoy state in terms of key generation rate and distance. We demonstrate an unconditionally secure key rate of 9.7008 × 10-4 per pulse for a 25 km fiber length